2014
DOI: 10.4171/125-1/5
|View full text |Cite
|
Sign up to set email alerts
|

Ordered exchange graphs

Abstract: Abstract. The exchange graph of a cluster algebra encodes the combinatorics of mutations of clusters. Through the recent "categorifications" of cluster algebras using representation theory one obtains a whole variety of exchange graphs associated with objects such as a finite-dimensional algebra or a differential graded algebra concentrated in nonpositive degrees. These constructions often come from variations of the concept of tilting, the vertices of the exchange graph being torsion pairs, t-structures, silt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
79
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(80 citation statements)
references
References 77 publications
1
79
0
Order By: Relevance
“…Moreover, we denote by CEG * (S) the exchange graph of reachable cluster tilting sets of C (S), that is, the connected unoriented graph whose vertices are the reachable cluster tilting sets and whose edges are the mutations. We refer to [4] for more details on and equivalent definitions of the graph CEG * (S). Let C × (S) be the set consisting of objects that appear in some cluster tilting set P in CEG * (S).…”
Section: Preliminariesmentioning
confidence: 99%
“…Moreover, we denote by CEG * (S) the exchange graph of reachable cluster tilting sets of C (S), that is, the connected unoriented graph whose vertices are the reachable cluster tilting sets and whose edges are the mutations. We refer to [4] for more details on and equivalent definitions of the graph CEG * (S). Let C × (S) be the set consisting of objects that appear in some cluster tilting set P in CEG * (S).…”
Section: Preliminariesmentioning
confidence: 99%
“…More recent work (see [9] and the many references therein) has shown that exchange graphs of many cluster algebras can be modeled using many different representation theoretic objects related to certain Jacobian algebras Λ [21]. In particular, the poset of functorially finite torsion pairs in the module category of Λ and the poset of 2-term simple-minded collections in the bounded derived category of Λ are isomorphic to the oriented exchange graph [7] of the cluster algebra defined by the quiver of Λ.…”
mentioning
confidence: 99%
“…torsion-free part) generated (resp. cogenerated) by indecomposable Λ-modules M with dimpM q (resp.´dimpM q) a row vector of C (see [9] for a proof that these maps are bijections when Λ is a finite dimensional Jacobian algebra).…”
mentioning
confidence: 99%
“…The set c-matpQq can be regarded as a directed graph whose vertices are c-matrices and whose directed edges are exactly those of the form C Q Ñ C µ k Q where c k P C Q is positive. Now by regarding c-matpQq as a directed graph, it follows from [7] that Ý Ý Ñ EGp p Qqc-matpQq and maximal directed paths in each are in natural bijection. 1 Moreover, each directed edge C Q Ñ C µ k Q of c-matpQq is labeled by the c-vector c k .…”
Section: 2mentioning
confidence: 99%
“…Perhaps surprisingly, the c-matrices and g-matrices of a quiver can be obtained from each other by a simple bijection, as the following theorem shows. [7,Theorem 4.17]) The map c-matpQq ÝÑ g-matpQq C Þ ÝÑ pC´1q T pG´1q T ÐÝ G sending a c-matrix or g-matrix to its inverse transpose is a bijection, and this map commutes with mutation of c-matrices and g-matrices of Q.…”
Section: 2mentioning
confidence: 99%